Migrants' human rights and health protection during the COVID-19 pandemic in the Mediterranean Sea: what we have learnt from direct inspections in two Italian hotspots - Cristoforo Pomara; Cristoforo Pomara; Salvatore Angelo Zappalà; Monica Salerno; Francesco Sessa; Massimiliano Esposito; Giuseppe Cocimano; Salvatore Ippolito; Alessandro Miani; Alessandro Miani; Eduardo Missoni; Prisco Piscitelli (Frontiers Media S.A., 2023)
This study aims to assess the situation of Italian hotspots for migrant reception during the COVID-19 pandemic, and specifically analyzing the situation of two hotspots located in the Sicily Region (Pozzallo harbor and Lampedusa Island), to identify critical issues. At the same time, we hypothesize solutions to guarantee the respect of human rights and suggest an operational protocol to be applied in similar situations, considering that the migration phenomenon is increasing and involving new geographical areas. Based on data obtained through the site inspections, the facilities of Pozzallo and Lampedusa exceeded their capacity to adequately contain the spread of the SARS-CoV-2 infection. Considering these findings, we suggest a practical workflow summarizing the main actions that should be applied to contain COVID-19, or other infectious disease, spreading in hotspots for migrants. The impact of the COVID-19 pandemic on migrants has received limited attention, although the migration phenomenon did not slow down during the pandemic period. Regarding the risk of spreading infectious diseases such as COVID-19, it is necessary that those countries who are most exposed to migration flows, such as Italy, plan dedicated strategies to minimize the possibility of transmission of SARS-CoV-2, using adequate protocols to monitor the possible insurgence of variants of interest (VOIs) or variants of concern (VOCs). Finally, it is important to state that these suggestions could be applied in any future pandemics.